(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article introduces the complexity of medical terminology and its prevalence in everyday life, emphasizing that understanding it is crucial for navigating medical contexts. The main aim of the article is to demystify medical terminology, making it accessible and understandable to a broad audience. It asserts that with a grasp of its basic structure, even complex medical terms can become comprehensible. Medical terminology is defined as the specialized language used within the medical profession. It encompasses a wide range of terms related to the human body, including its anatomy, physiology, diseases, treatments, and procedures. The article explains the methodology of medical terminology, focusing on its morphological structure. It clarifies that medical terms are typically constructed from a combination of prefixes, root words, combining vowels, and suffixes, mostly derived from Latin.